Baroque Oboe - Ayşin Pelin Kiremitci (Konservatoryum)
Oboe is a double-reed, wooden wind instrument that is not well known in our country, but whose ancestors have a long history in these lands. Oboe, a derivative of the zurna, which has a great role in the history and cultural structure of the Turkish people, comes to mind as a very different, large and deep-voiced instrument due to the low vowels in its name. However, the oboe is a delicate instrument defined as a soprano instrument in modern orchestras. This work; It includes the evolution of the zurna, an instrument integrated with the Turkish people, into the oboe, or Baroque Oboe as it was called at the time, during the European adventure. Before this study, foreign sources about oboe and wind instruments were scanned, libraries, music and instrument magazines, encyclopedias and websites were searched. Since it is necessary to know the old instruments that are similar to the oboe in order to understand the music of the old period and their interpretation styles, the study was not limited to the Baroque Period, but the first examples of double-reed wooden wind instruments were also used in the pre-Baroque period. A simple form of expression was used in order to create a Turkish resource for oboe students. In addition, this study is intended to be a resource that will shed light on the capacity of the instrument for composers or composition students who want to write works for the baroque oboe.